Satisfaction evaluation of flash glucose monitoring system in early glucose management of patients after kidney transplantation - Guo, Jiayu; Qin, Ming; Li, Jinke; Zhou, Jiangqiao; Qiu, Tao; Tang, Yan (Frontiers in Medicine, 2025)
AimTo study the effectiveness of the flash glucose monitoring (FGM) system in the monitoring of blood glucose in patients after renal transplantation.MethodsOne hundred and fifteen patients who underwent renal transplantation at the Renmin Hospital of Wuhan University from January to December 2021 were selected for the study, with patients from January to June as the control group (n = 62) and patients from July to December as the observation group (n = 53). The control group used traditional finger blood collection to monitor blood glucose, while the observation group used FGM system to monitor the patients' blood glucose. The Digital Pain Rating Scale (NRS) and the Glucose Monitoring System Satisfaction Questionnaire (GMSS) were used to compare the pain associated with glucose needling and patient satisfaction with the glucose monitoring equipment, and compared the incidence of abnormal blood glucose events and adverse events between the two groups.ResultsThe differences in pain comparison, satisfaction with the blood glucose monitoring equipment, the number of abnormal blood glucose events and adverse events between the two groups were statistically significant (p < 0.05).ConclusionThe application of FGM system enables continuous glucose monitoring and management of patients in the early post-transplant period, reduces the painful pinprick of glucose monitoring, detects glucose abnormalities early, reduces adverse events and improves patient satisfaction.